38 Building Research Capacity: The Impact of The Brain Tumour Charity’s Future Leaders Funding Programme - Lucy Grist; Simon Newman; Emma Thompson (Neuro-Oncology, 2026)
Abstract Introduction Brain tumours remain one of the most challenging cancers, and progress is slowed by a shortage of researchers entering and remaining in the field. To build capacity, ensure research excellence and drive innovation, The Brain Tumour Charity established the Future Leaders Programme to identify talented early‑career researchers and support them to become leaders in brain tumour research. Methods The programme uses a staged funding model. Researchers undertake a three‑year Postdoctoral Fellowship, receiving £75,000 pa to build research skills and deliver high‑impact projects. This is followed by an invitation to apply for a four‑year Junior Fellowship, which provides £600,000 over four years. One Junior Fellow will then receive support totalling £1M in a five-year Senior Fellowship. Throughout this pathway, The Charity provides training, networking opportunities, and support. Results Assessing both the person and excellence of the science has proved extraordinarily successful, with many Future Leaders starting their own labs and driving clinical trials. The programme has supported a diverse portfolio of innovative projects. These include immune‑based approaches targeting IL‑10, blood‑based biomarkers to detect tumour recurrence, engineered “smart viruses”, and research defining the origins of meningioma. Our newest Junior Fellows, Dr. Ola Rominiyi and Dr. Christopher Mount, are advancing work on DNA repair mechanisms and CAR‑T cell therapy to address treatment resistance and accelerate immunotherapy development. Conclusions The Future Leaders programme provides sustained investment, structured career development, and an innovation‑focused environment. By empowering early‑career researchers to pursue ambitious projects, it accelerates discovery and contributes to improving outcomes for people affected by brain tumours. By 2030 almost 30 researchers will have passed through the scheme and form our wider Future Leaders Network, driving the research collaborations and discoveries of the future.